2006
DOI: 10.2337/db05-1607
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Signal-Regulating Kinase 1 Mediates Cellular Senescence Induced by High Glucose in Endothelial Cells

Abstract: 1Vascular ageing is accelerated in patients with diabetes. However, the underlying mechanism remains unclear. Here, we show that high glucose induces activation of apoptosis signal-regulating kinase 1 (ASK1), an apoptosisinducing signal that mediates endothelial cell senescence induced by hyperglycemia. High glucose induced a timedependent increase in the levels of ASK1 expression and its activity in human umbilical vein endothelial cells (HUVECs). Incubation of endothelial cells with high glucose increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(116 citation statements)
references
References 43 publications
5
110
0
1
Order By: Relevance
“…27 We considered STZ-diabetic mice suitable for investigation of clinical settings. STZ-treated mice with and without pitavastatin administration had elevated plasma glucose associated with decreased plasma insulin level compared with control mice (Supplemental Figure IVA).…”
Section: Administration Of Pitavastatin Inhibits Vascular Endothelialmentioning
confidence: 99%
“…27 We considered STZ-diabetic mice suitable for investigation of clinical settings. STZ-treated mice with and without pitavastatin administration had elevated plasma glucose associated with decreased plasma insulin level compared with control mice (Supplemental Figure IVA).…”
Section: Administration Of Pitavastatin Inhibits Vascular Endothelialmentioning
confidence: 99%
“…Third, high FPG levels have been shown to induce activation of signaling involved in endothelial apoptosis. 21 Fourth, hyperglycemic individuals are hyperinsulinemic, and the high insulin levels may promote increased ventricular mass and decreased cardiac output. 22 Fifth, hyperglycemic individuals also are insulin resistant, which is an independent predictor of incident CHF after accounting for diabetes or obesity.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…The role of the well known tumour suppressor transcription factor p53 in diabetes has long been undervalued. Research has recently focused on p53 activation in human endothelial cells exposed to high glucose levels [14], showing how p53-induced cellular senescence in vascular cells might contribute to accelerated ageing and atherosclerosis [15,16]. Furthermore, studies showed that inhibition of p53 activity in mouse adipose tissue markedly decreased the expression of proinflammatory cytokines and improved insulin resistance in mice with type 2 diabetes-like disease.…”
Section: Introductionmentioning
confidence: 99%